Measurement and Mitigation of Intracochlear Pressure Transients During Cochlear Implant Electrode Insertion. Issue 2 (February 2022) - Banakis Hartl, Renee M.; Greene, Nathaniel T.
Abstract : Hypothesis: High intracochlear pressure transients associated with cochlear implant placement are reduced with smaller, non-styleted arrays, and longer insertion durations. Background: With increasing focus on hearing preservation during cochlear implant surgery, atraumatic technique is of the utmost importance. Previous studies revealed that high intensity pressure transients can be generated during the insertion of implant electrodes. Resulting acoustic trauma may be one contributing factor to postoperative loss of residual hearing. Methods: Thirty ears in cadaveric specimens were surgically prepared with placement of intracochlear pressure sensors. Sequential implant insertions were made over 10, 30, or 60 seconds using seven randomly ordered electrode styles. Pressures were also measured during common post-insertion electrode manipulations and removal. Measurements were compared between electrode styles and characteristics using analysis of variance (ANOVA) and Pearson correlation. Results: Implant insertion and post-insertion manipulations produced high-intensity pressure transients with all electrodes tested, with some measurements exceeding 170 dB peak SPL. Average peak pressures were significantly lower for straight, non-stylet electrodes ( p  << 0.001). The likelihood of generating transients was lowest with the slowest insertions ( p  << 0.001). Conclusions: Cochlear implant insertion can generate transients in intralabyrinthine pressure levels equivalent to high intensity, impulsive acoustic stimuli known to cause hearing loss. Although transients were observed in all conditions, exposure may be mitigated by using non-styleted electrodes and slow insertion speeds. Additional surgical manipulations can also produce similar high-pressure events. Results from this investigation suggest that use of non-styleted electrodes, slow but steady insertion speeds, and avoidance of post-insertional manipulations are important to reduce cochlear trauma. Abstract : Supplemental Digital Content is available in the text